(untitled) (Applied Biological Research, 2015)
A thermophilic bacterium Aneurinibacillus thermoaerophilus MCW220 producing extracellular thermostable protease was isolated from Manikaran hot water spring, Himachal Pradesh (India). Till date there is no report of thermostable protease production by any Aneurinibacillus thermoaerophilus. The strain MCW220 was characterized morpho biochemically followed by sequencing of its 16S rRNA gene. BLASTn search analysis of the sequence showed maximum identity with A. thermoaerophilus L420-91 and the G + C content was 57.2%. The A. thermoaerophilus MCW220 when quantitatively screened for protease activity showed maximum thermostable protease activity of 33.4 U L-1. The optimum yield and maximum protease activity was achieved at 48 h incubation, with pH 7.0 at 60ºC. The desired protein was precipitated and purified from the crude extract by using ammonium sulfate (80%) and Sephadex G-100 column. The procedure yielded 0.105 g protein with 2.35 fold purification with a yield 54.16%. The molecular mass of enzyme was found 45 kDa by SDS-PAGE. Purified protease showed maximum enzyme activity within the pH range of 9.0-9.5 at 50oC and possessed compatibility with various detergents which make it a potential candidate for use in detergent industry.